Comparative genotoxicity as a baseline protocol for assessing environmental quality in Brazilian Marine Protected Areas: A case study of Grapsus grapsus (Brachyura: Grapsidae) from Trindade and Fernando de Noronha islands - Adam, Mônica L.; Torres, Rodrigo A.; Boos, Harry; Lima, Anderson R.B.; Pinheiro, Marcelo A.A. [UNESP] (Elsevier, 2025)
Marine Protected Areas (MPAs) aim to preserve the existing biological richness. However, anthropic actions can compromise the stability of the ecosystem even in areas of environmental protection. The present study aimed to evaluate the environmental quality of two Brazilian MPAs, the Natural Monument of the Islands of Trindade and Martim Vaz and of Mount Columbia and the Marine National Park of Fernando de Noronha, through the evaluation of genomic damage in hemocytes of the rocky crab Grapsus grapsus. The results indicated an environmental impact on the island of Fernando de Noronha, on the two evaluated beaches (Sueste and Sancho), demonstrated by high levels of micronucleated cells observed in the sampled animals. The likely explanation for this impact refers to the intense tourist activity on the island. Trindade Island was shown to be well preserved, with animals presenting basal levels of expression of genome damage possibly due to the minor human presence in the island and due to its distance from coastline (diluted pollutants). The results presented here highlight contrasting environmental circumstances in terms of effectiveness of conservation actions in Brazilian MPAs. In addition, the results also reaffirmed the accuracy of the environmental impact assessment protocol using the genome damage parameters to diagnose and monitoring the environmental quality.